Gap in gender equality in secondary education classrooms. Artistic education - Vernia Carrasco, Ana M. (Journal of Learning Styles, 2024)
Artistic education is not just entertainment, its benefits are already known from multiple and different investigations. On the other hand, education cannot be understood in a fragmented way. Employability, transformation, co-education, innovation or creativity are part of the comprehensive training of people, trying to avoid any gap in gender equality. Our proposal is based on research in the field of secondary education and with the collaboration of teacher-students of music, plastic and visual arts and physical education. The theoretical framework supported the hypothesis about the need to take music as an interdisciplinary subject to improve educational quality, within the framework of attention to gender equality. A mixed qualitative-quantitative was chosen, with a small sample. The results indicate that there is still a gap regarding gender equality associated with some educational activities. The conclusions led us to propose, on the one hand, a necessary reflection on the curriculum, and on the other hand, the possibility of including an option aimed at improving training regarding coeducation. In relation to the Sustainable Development Goals (SDG), music education is considered as a facilitating tool for interdisciplinarity between the arts and other subjects of secondary education.